The Effectiveness of a Scientific Approach in Discus Throw Learning to Improve Students’ Motor Skills - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study investigates the effectiveness of the scientific approach in enhancing students’ motor skills in discus throw learning at SMP Negeri 24 Makassar. A quasi-experimental design was employed with two groups: an experimental group taught using the scientific approach and a control group taught using conventional methods. A total of 60 eighth-grade students were selected through purposive sampling. Pretest and posttest were conducted to assess motor skill development. Descriptive data indicated that the experimental group improved from a mean pretest score of 65.40 to a posttest score of 80.73, while the control group increased from 64.80 to 68.63. Normality and homogeneity tests confirmed that the data were suitable for further analysis. The paired sample t-test revealed a significant improvement in the experimental group (p < 0.05), and the independent sample t-test showed a significant difference between the posttest scores of the two groups (t = 6.72, p < 0.05). The calculated Cohen’s d of 2.06 indicated a large effect size. The findings suggest that the scientific approach is significantly more effective in improving motor skills in discus throw learning than conventional methods. It is recommended for broader application in physical education to enhance student engagement and performance.